Оптимізація пропускної здатності в системах пакетної обробки даних - Денисов, Р. К. (ХНУРЕ, 2024)
This paper proposed an optimization of throughput in the Batch-Processing Systems, specifically in a closed queueing system with clients and m servers. Generally, clients are producing jobs that are processed in batches by parallel servers. The main characteristics that impact system throughput are batch size and corresponding speedup function. In such systems, the speedup function has the sub-additive property that means that infinitely increased computational resources will not affect the efficiency linearly. In fact, the problem of throughput optimization leads to searching for the optimal batch size parameter. The process of finding the batch size parameter could take up to multiple weeks in existing big tech systems. This paper has strived to find optimal throughput in O(1) time by referring to the mean-field model (MFM).
Keywords: пакетна обробка даних; оптимізація пропускної здатності